(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Nutritional deficiencies pose significant health risks and are prevalent among diverse populations. Pharmacists, as accessible healthcare providers, play a pivotal role in identifying, assessing, and managing these deficiencies. This abstract presents a guide for pharmacists to effectively address nutritional deficiencies in their practice. Key components include understanding common deficiencies, screening and assessment techniques, patient education and counseling strategies, pharmacological interventions, monitoring and follow-up protocols, considerations for special populations, and the importance of collaborative care. By integrating these components into pharmacy practice, pharmacists can enhance patient outcomes and contribute to improved health in their communities.